Combined deficiency of PI3KC2α and PI3KC2β reveals a nonredundant role for PI3KC2α in regulating mouse platelet structure and thrombus stability. (3rd July 2016) - Petitjean, Claire; Setiabakti, Natasha M.; Mountford, Jessica K.; Arthur, Jane F.; Ellis, Sarah; Hamilton, Justin R.
Abstract: The physiological functions and cellular signaling of Class II phosphoinositide 3-kinases (PI3Ks) remain largely unknown. Platelets express two Class II PI3Ks: PI3KC2α and PI3KC2β. PI3KC2α deficiency was recently reported to cause disruption of the internal membrane reserve structure of platelets (open canalicular system, OCS) that results in dysregulated platelet adhesion and impaired arterial thrombosis in vivo . Notably, these effects on platelets occurred despite normal agonist-induced 3-phosphorylated phosphoinositide (3-PPI) production and cellular activation in PI3KC2α-deficient platelets. However, the potential compensatory actions of PI3KC2β in platelets have not yet been investigated. Here, we report the first mice deficient in both PI3KC2α and PI3KC2β (no Class II PI3Ks in platelets) and reveal a nonredundant role for PI3KC2α in mouse platelet structure and function. Specifically, we show that the disrupted OCS and impaired thrombus stability observed in PI3KC2α-deficient platelets does not occur in PI3KC2β-deficient platelets and is not exaggerated in platelets taken from mice deficient in both enzymes. Furthermore, detailed examination of 3-PPI production in platelets from this series of mice revealed no changes in either unactivated or activated platelets, including those with a complete lack of Class II PI3Ks. These findings indicate a nonredundant role for PI3KC2α in regulating platelet structure and function, and suggest that Class II PI3Ks do not significantly contribute to the acute agonist-induced production of 3-PPIs in these cells.